Attenuation of cardiovascular responses to laryngoscopy and intubation –A comparative study between IV esmolol hydrochloride and lignocaine hydrochloride - Eswari Prasanna P,; Katika Surya Gowthami,; Asha Latha A,; Rajendra Prasad M, (Asian Journal of Medical Sciences, 2022)
Background: Laryngoscopy and tracheal intubation are frequently associated with sympathetic stress response. Lignocaine and esmolol are useful to decrease the sympathetic response to laryngoscopy and intubation. Aims and Objectives: The aim of the study was to study the effectiveness of lignocaine and esmolol administered intravenously before laryngoscopy and intubation in attenuating the sympathetic response. Materials and Methods: The prospective, randomized, and controlled study was conducted in Maharajah’s Institute of Medical Sciences Hospital for a period of 18 months from January 2016 to June 2017. A clinical comparative study of attenuation of sympathetic response to laryngoscopy and intubation was done in 90 patients posted for elective surgeries. The sample size estimation is calculated based on findings from the previous study done by Singh et al., (2013).Group I was control group. In this group, no drug was administered. Group II was lignocaine group. Here, patients received 1.5mg/kg lignocaine i.v. bolus. Group III was esmolol group. All patients in this group received 2mg/kg i.v. bolus. Statistical Analysis: Descriptive data presented as Mean±SD and in percentage. Pair-wise comparison between the groups was done by “Z” test. For all tests,“Z” value of >1.96 was considered significant and “P’ <0.05” was considered significant. Results: Esmolol at a bolus dose of 2mg/kg i.v. administered 3 min before laryngoscopy and intubation is more efficient than lignocaine given at a dose of 1.5mg/kg. Conclusions: Esmolol at bolus dose of 2mg/kg i.v. administered can be recommended to attenuate sympathetic responses due to laryngoscopy and intubation.